A)5(5+2a)+2akwadrat-(5+a)kwadrat-5b

b)(0,5a-b)kwadrat+b(a-b-5)+0,75akwadrat

c)20a+(2a+5)kwadrat-5(5+b)-3akwadrat

d)(0,5a-0,25b)kwadrat*32-4Bkwadrat

e)b+(5a-b)kwadrat-0,5a-5(5akwadrat-2ab)-bkwadrat

f)-(a-b)(a+b)+(a+b)(a-b)+0,5a-b

g)(5a-b)(5a+b)-8abkwadrat+bkwadrat-17akwadrat

h)(a-b)kwadrat+2ab-2bkwadrat-(a-b) (a+b)+0,5a-b

i)(-a-b)kwadrat+0,5a-(a+b)kwadrat+4ab+(-b)

Pozdrawiam!!

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-13T16:39:13+01:00
A)5(5+2a)+2akwadrat-(5+a)kwadrat-5b=25+10a+2a²-(25+10a+a²)-5b=25+10a+2a²-25-10a-a²-5b=a²-5b
b)(0,5a-b)kwadrat+b(a-b-5)+0,75akwadrat=0,25a²-b²+ba-b²-5b+0,75a²=a²-2b²-5b+ba
c)20a+(2a+5)kwadrat-5(5+b)-3akwadrat=20a+4a²+20a+25-25-2b-3a²=a²+40a-2b
d)(0,5a-0,25b)kwadrat*32-4Bkwadrat=(0.25a²-2ab+0.0625b)*32-4b²=8a²-64ab+2b-4b²=8a²+2b-4b²-64b
e)b+(5a-b)kwadrat-0,5a-5(5akwadrat-2ab)-bkwadrat=b+25a²-10ab+b²-0,5a-25a²+10ab=0,5a+b+b²
f)-(a-b)(a+b)+(a+b)(a-b)+0,5a-b=-a²-ab+ab+b²+a²-ab+ab-b²+0,5a-b=0,5a-b
g)(5a-b)(5a+b)-8abkwadrat+bkwadrat-17akwadrat=25a²+5ab-5ab-b²-8a²+b²=17a²
h)(a-b)kwadrat+2ab-2bkwadrat-(a-b) (a+b)+0,5a-b=a²-2ab+b²+2ab-2b²-a²-ab+ab+b²+0,5a-b=0,5a-b+2ab
i)(-a-b)kwadrat+0,5a-(a+b)kwadrat+4ab+(-b)=a²+2ab+b²+0,5a-a²-b²+4ab-b=0,5a-b+6ab
2010-03-13T16:41:34+01:00
A)5(5+2a)+2a²-(5+a)²-5b=
=25+10a+2a²-25-a²-5b-10a=
=2a²-a²-5b+10a-10a=
=a²-5b

b)(0,5a-b)²+b(a-b-5)+0,75a²=
=0,25+b²+ab-b²-5b+0,75a²=
=0,75a²+ab-5b+0,25


c)20a+(2a+5)²-5(5+b)-3a²=
=20a+4a²+25-25-5b-3a²=
=4a²-3a² + 20a-5b=
=a²+20a-5b

d)(0,5a-0,25b)²*32-4B²=
=0,25a²+0,0625b²*32-4b²=
=0,25a²+2b-4b²=
=-4b²+0,25a²+2b

e)b+(5a-b)²-0,5a-5(5a²-2ab)-b²=
=b+25a²+b²-0,5a-25a²+10ab-b²=
=b²-b²+25a²-25a²+10ab-0,5a+b=
=10ab-0,5a+b

f)-(a-b)(a+b)+(a+b)(a-b)+0,5a-b=
=(b-a)(a+b)+a²-b² + 0,5a-b=
=b²-a²+a²-b² +0,5a-b=
=0,5a-b

g)(5a-b)(5a+b)-8ab²+b²-17a²=
=25a²-b²-8ab²+b²-17a²=
=25a²-17a²-b²+b² -8ab²=
=8a²-8ab²

h)(a-b)²+2ab-2b²-(a-b) (a+b)+0,5a-b=
=a²+b² +2ab-2b²+(b-a)(a+b)+0,5a-b=
=a²+b² +2ab-2b²+b²-a²+0,5a-b=
=a²-a²+b²+b²-2b²+2ab+0,5a-b=
=2ab+0,5a-b

i)(-a-b)²+0,5a-(a+b)²+4ab+(-b)=
=a²+b²+0,5a-(a²+b²) + 4ab-b=
=a²-a²+b²-b² +4ab - b + 0,5a=
=4ab - b + 0,5a
2010-03-13T16:43:36+01:00
A) 25+10a+2akwadrat-(5+a)(5+a)-5b=
25+10a+2akwadrat-25-5a-5a-akwadrat-5b=
akwadrat-5b
b) (0,,5a-b)(0,5a-b)+ab-bkwadrat-5b+0,75akwadrat=
0,25akwadrat-0,5ab-0,5ab+bkwadrat+ab-bkwadrat-5b+0,75a=
0,25akwadrat-5b+0,75akwadrat
c) 20a+4akwadrat+10a+10a+25-25-5b-3akwadrat=
40a+akwadrat-5b
d) (0,25akwadrat-0,125ab-0,125ab+0,5bkwadrat)*32-4bkwadrat=
8akwadrat-4ab-4ab+16bkwadrat-4bkwadrat=
8akwadrat-8ab+12bkwadrat
e) b+25akwadrat-5ab-5ab+bkwadrat-0,5a-25akwadrat+10ab-bkwadrat
b-0,5a
f) -(akwadrat+ab-ab-bkwadrat)+akwadrat-ab+ab-bkwadrat+0,5a-b=
-akwadrat-ab+ab+bkwadrat+akwadrat-ab+ab-bkwadrat+0,5a-b=
0,5a-b
g) 25akwadrat+5ab-5ab-bkwadrat-8abkwadrat+bkwadrat-17akwadrat=
8akwadrat-8abkwadrat
h) akwadrat-ab-ab+bkwadrat+2ab-2bkwadrat-(akwadrat+ab-ab-bkwadrat)+0,5a-b=
akwadrat+bkwadrat-2bkwadrat-akwadrat-ab+ab+bkwadrat+0,5a-b=
0,5a-b
i)akwadrat+ab+ab+bkwadrat+0,5a+akwadrat+ab+ab+bkwadrat+4ab-b=
2akwadrat+8ab+2bkwadrat+0,5a-b

:)